Corporate Environmental Crime: An Islamic Criminal Law and Criminological Perspective - Wiji Nur Eko Wahyu; Abdul Halim; Risnita Risnita (International Journal of Law and Society, 2026)
Particularly in emerging nations, corporate environmental criminality poses a serious threat to environmental justice, sustainable development, and legal responsibility. With a focus on corporate crime theory and green criminology, this study critically analyzes corporate environmental crime using an integrative framework that blends modern criminological viewpoints with Islamic criminal law (fiqh al-jināyah). This study examines how Islamic legal concepts, particularly the doctrine of maqāṣid al-sharī‘ah, can enhance current models of corporate criminal responsibility and environmental governance using a normative-analytical and conceptual approach. The results show that structural incentives, lax enforcement, and profit-driven rationalization tactics make traditional regulatory and penal measures ineffective at discouraging corporate environmental malfeasance. Islamic criminal law provides a revolutionary framework that places environmental conservation as both a legal requirement and a moral necessity because of its strong ethical orientation and comprehensive view of justice. With a focus on ecological balance (ḥifẓ al-bi’ah), property (ḥifẓ al-māl), and life preservation (ḥifẓ al-nafs), this study offers a value-based corporate accountability approach that goes beyond deterrence-oriented punishment and prioritizes prevention, restoration, and social responsibility. By broadening the doctrinal scope of Islamic criminal law to acknowledge corporate criminal culpability, this integrative approach makes a theoretical contribution. Practically, it informs regulatory enforcement and environmental policy change. The study presents an interdisciplinary paradigm that unites criminological analysis and religious legal reasoning, providing a strong basis for creating environmental governance systems that are just, moral, and sustainable, especially in developing nations and jurisdictions with a majority of Muslims.